Emerging problematics of deregulating the urban: The case of permitted development in England. (August 2021) - Ferm, Jessica; Clifford, Ben; Canelas, Patricia; Livingstone, Nicola
Urban planning systems, processes and regulations are often blamed – by many mainstream economists – for constraining the supply of housing by interfering with the efficient allocation of land by the market and unnecessarily delaying development. In England, this orthodox view has influenced the government's deregulatory planning reforms, including – since 2013 – the removal of the requirement for developers to apply for planning permission for the conversion of an office building to a residential one (making it 'permitted development'). Drawing on original empirical research in five local authority areas in England, this article examines the impacts of this deregulation of planning control on the ground. We find that, although more housing units have been delivered than were expected, a focus on housing numbers is eclipsing problems of housing quality, the type of housing being made available and whether it is in sustainable locations. There are also costs of deregulating planning, including direct financial costs and the lost opportunity to secure affordable housing and public infrastructure through planning gain. We conclude by examining the contradictions in the UK government's approach to addressing the housing crisis and propose there are dangers of deregulating the urban that have consequences for England and other countries pursuing neoliberal reforms.